Chemokine (C-C motif) ligand 2 and chemokine (C-C motif) ligand 7 in angle-closure glaucoma - Gao, Xinbo; Jonas, Jost B. (Acta ophthalmologica, 2016)
Purpose To compare the concentrations of chemokine (C-C motif) ligand 2 (CCL2) and chemokine (C-C motif) ligand 7 (CCL7) in aqueous humour of eyes with acute primary angle-closure (APAC), primary angle-closure glaucoma (PACG) or with age-related cataract. Methods The prospective investigation included a study group of 56 patients (24 patients with APAC; 32 patients with PACG) undergoing glaucoma surgery and a control group of 21 patients undergoing routine cataract surgery. The interval between glaucoma attack and trabeculectomy was 19.4 ± 9.8 days. Results The concentrations of CCL2 (3037 ± 501 versus 1127 ± 141 pg/ml; p = 0.003) and CCL7 (10.5 ± 2.4 versus 2.8 ± 0.4 pg/ml; p < 0.001) were significantly higher in the APAC group than in the PACG group, while the concentrations of both cytokines did not differ significantly between the PACG group and the control group (CCL2: 1190 ± 98 pg/ml; p = 0.10; CCL7: 2.0 ± 0.6; p = 0.18). The concentrations of both cytokines were significantly and inversely correlated with the interval between the acute angle-closure attack and surgery (CCL2: p = 0.02; ρ = -0.48; CCL7: p = 0.04; ρ = -0.42). Higher CCL2 concentrations were associated with higher prevalence of surgical failure (28.6% versus 7.1%; p = 0.036). Conclusions Concentrations of CCL2 and CCL7 as major inflammatory cytokines with potential influence on the risk of filtering surgery failure were significantly elevated after an acute glaucoma attack and decreased with longer interval to the attack. Trabeculectomy may have a lower risk of failure if performed later than earlier after an acute glaucoma attack, with lower CCL2 concentrations associated with better surgical outcome.